Study of FVC,FEV1 & FEV1/FVC% in adult male smokers (Bangladesh Journal of Medicine, 2015)
Background: Smoking is most common in East Asia, where two thirds of all adult male smoke tobacco; cigarette smoking is by far the most common. Smoking is the primary cause of chronic obstructive lung disease, chronic bronchitis and other respiratory symptoms. Many studies have shown a significant change of FVC,FEV1 &FEV1/FVC% in adult smokers. Objective: To assess the change of FVC,FEV1 & FEV1/FVC% in adult male smokers. Method: This cross-sectional comparative study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka and National institute of Diseases of Chest and Hospital, Dhaka during the period of 1st July, 2007 to 30th June, 2008. For this purpose, 160 adult male subjects ranging from 18 to 52 years were selected. The subjects were divided into two groups - A and B. Group A consisted of 40 apparently healthy adult male non-smokers. Group B consisted of 120 apparently healthy adult male smokers. The experimental group was again subdivided into group B1 consisting of 40 smokers consuming 2-10 cigarettes/day for more than 5 years, group B2 consisting of 40 smokers consuming 11-20 cigarettes/ day for more than 5 years and group B3 consisting of 40 smokers consuming >20 cigarettes/day for more than 5 years. Analysis of data was done with the help of computer by SPSS 12.0 programmer and significant tests were done by unpaired students t test. Results: There were no statistically significant differences of FVC,FEV1 in group A vs. group B1, group B2 vs. group B3. The mean FVC,FEV1 were significantly lower (